The role of oral mifepristone in pre-induction cervical ripening at term - Chourasia, Uma H.; Jain, Mudita Kamlesh; Fidvi, Juzar I. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Planned induction of labor is an established part of modern obstetrics and is used as a definite form of treatment where continuation of pregnancy would be detrimental to the health of mother or fetus. The objective of this study was to evaluate the effect of mifepristone in pre-induction cervical ripening and labor induction. Methods: A total of 200 pregnant women at term with Bishop Score 4 or less were selected for this prospective randomized placebo-controlled study. The sample was equally divided into study group to receive 200 mg of mifepristone and control group to receive placebo orally for 2 days. Bishop score was assessed at every 24 hours interval till patient entered in spontaneous labor or 72 hours after 1st dose. Women who did not enter labor spontaneously, labor induction was planned with per vaginal insertion of prostaglandin (PG) E2 analogue, Dinoprostone gel 2.5 mg or PGE1 analogue Tab. Misoprostol 25 µg. Results: Ninety-six subjects in the study group and eighty-one in the control achieved successful ripening of cervix and the difference was statistically significant. Sixty-eight of study group and thirty-nine of placebo group entered in spontaneous active labor within 72 hours. Requirement of oxytocin as adjuvant treatment was significantly lower in the study group. Nineteen women of study group and fifteen of control group delivered within 24 hours, and eighty-one of study group and sixty-two of placebo delivered in 48 hours. The mean induction delivery interval was 35.53±13.67 hours in the study group, whereas it was significantly prolonged in the placebo group 50.49±20.92 hours. Eighty-two subjects of study group and seventy-eight of the control group delivered vaginally, the differences were statistically not significant. Conclusions: Mifepristone was found to be an effective agent for cervical priming prior to labor induction in women at term and significantly reduces the induction delivery interval compared with placebo.